Sikap guru Sekolah Menengah Daerah Pekan Pahang terhadap pusat sumber sekolah - Norizan, binti Ismail (1997)
The main objective of this study was to observe differences in knowledge and attitude of teachers towards the roles and activities of the School Resource Centre based on their gender, age, teaching experience and professional qualifications. It was also undertaken to identify the relationship between teacher's knowledge of the roles of the Centre and attitude of teachers toward activities run by it. The subjects of the study were 217 teachers from eight secondary schools in the district of Pekan, Pahang